Young Puritans: Adolescent Abstainers and Mental Health. Issue 2 (1st February 2021) - Chen, Jing; Forsyth, Craig J.; Biggar, Raymond W.
ABSTRACT: This paper uses data from 2016 Caring Communities Youth Survey (CCYS) to examine adolescent abstainers from both drugs and antisocial behaviors. Four grade levels (6, 8, 10, 12) with an N = 79, 988 are analyzed. Prior research has defined the abstainer from only a limited number of drugs and/or antisocial behaviors. The present model uses all drugs and anti-social behaviors to describe the abstainer. The paper addresses the debate regarding adolescent abstainers. Are they loners with mental health issues? This research found that abstainers compared to all students have less mental health issues, less depression, and less purposefully hurting themselves behaviors such as cutting or burning. All findings were statistically significant.